2019
DOI: 10.3390/su11184868
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of Urban Green Areas for Quality of Life Improvement—Argument for Increased Citizen Participation

Abstract: Considering the imperative need for sustainable urban development, this article argues for increased citizen participation in the decision-making process, as it generates better outcomes (due to a wider range of perspectives) and also makes people better citizens, as they will be partially responsible for the results. One major dimension of urban areas’ which needs a sustainable development is represented by parks, which can be directly associated to citizens’ quality of life (QoL). Thus, we have conducted dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Green area is not only recognized as a suitable setting for running and jogging, but also for its potential in the alleviation of self-reported nervous problems and medication use [83]. In this sense, green area is considered as an important means by which to improve the quality of life of urbanites [84]. Indeed, empirical evidence has found that green area directly affects people's physical health and psychological well-being in a positive way, which may improve life satisfaction of residents [85].…”
Section: Hypotheses Development 21 the Relationship Between Community Engagement Flow Experience Green Area And Life Satisfactionmentioning
confidence: 99%
“…Green area is not only recognized as a suitable setting for running and jogging, but also for its potential in the alleviation of self-reported nervous problems and medication use [83]. In this sense, green area is considered as an important means by which to improve the quality of life of urbanites [84]. Indeed, empirical evidence has found that green area directly affects people's physical health and psychological well-being in a positive way, which may improve life satisfaction of residents [85].…”
Section: Hypotheses Development 21 the Relationship Between Community Engagement Flow Experience Green Area And Life Satisfactionmentioning
confidence: 99%
“…As Bednar [20] and Millimet [21] have stated, although the environmental federalism has received widespread attention worldwide, determining the optimal allocation of environmental authority at all levels of government remains a challenge. Considering the urgent need for sustainable urban development, Constantinescu et al [22] advocate increasing citizen participation in the decision-making process, as it can produce better results and can hold people accountable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several interlinkages between sustainable development goals (SDGs) and an even more significant number of targets are glocal [7] and compete for local public attention needing to be framed and incorporated both in state and local governments' programs and citizens' real life [8]. Recent contributions confirm urban sustainable development planning addresses citizens' concern about the quality of life and environmental protection by increasing their participation in policymaking processes and their involvement in designing nature-based and socially inclusive solutions [9][10][11]. What is commonly agreed upon is that participation can influence SDGs framing, meant as deliberate crafting.…”
Section: Introductionmentioning
confidence: 99%
“…As there can be simultaneously many ways of understanding a problem and finding solutions, according to the government and actors involved, participation is considered a suitable tool to elicit and mediate between distinct preferences and facilitate different and more adaptive solutions. Engaging citizens at the local level needs to rethink collaboration settings and partnerships [9] to better establish tools for integrating traditional approaches [10] to empower local communities in practice, allowing them to portray the context of sustainability better and build public acceptance in policymaking. Despite widespread support for public participation, there is no explicit consensus on the purpose or evidence of this practice's actual outputs and its effects on policy framing.…”
Section: Introductionmentioning
confidence: 99%